Review paperGenetic background of skin barrier dysfunction in the pathogenesis of psoriasis vulgaris - Stawczyk-Macieja, Marta; Szczerkowska-Dobosz, Aneta; Rębała, Krzysztof; Purzycka-Bohdan, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Psoriasis is a common inflammatory skin disease. It is known to be a complex condition with multifactorial mode of inheritance, however the associations between particular pathogenic pathways remain unclear. A novel report on the pathogenesis of psoriasis has recently included the genetic determination of the skin barrier dysfunction. In this paper, we focus on specific genetic variants associated with formation of the epidermal barrier and their role in the complex pathogenesis of the disease.